Importance and values on mental health in Ricardo Palma’s «El médico inglés» - Esquivel Ronceros, Deisy Alejandra (2020)
The purpose of this article is to analyse mental health in Peru from the 19th century onwards and to compare it with the current situation in the face of the arrival of the COVID-19 pandemic. At the same time, it seeks to report on how the lack of intervention by a specialist in the mental and social area leads citizens to a decline in their personality. Indeed, on the eve of the bicentenary, optimal emotional, psychological and social well-being should be achieved through attention to the mental health of every Peruvian. This is not the case due to the colonial heritage we still carry with us, which includes our slavery to marginality, rejection and selfishness, which deteriorates our beliefs and actions. For this reason, the story of Ricardo Palma’s «El médico inglés» is taken to highlight the concern for effective medical care, beyond physical health.